Monthly mowing frequency does not affect soil CO2 emissions of fertilized Bromus erectus‐dominated grasslands. (28th October 2022) - D'Ottavio, Paride; Francioni, Matteo; Toderi, Marco; Trozzo, Laura
Abstract: Secondary origin grasslands are widespread habitats that provide a wide array of ecosystem services. Their conservation relies on management practices that can, in turn, alter their soil carbon cycle to result in higher soil respiration rates. In the perspective of social and climate change scenarios, there is the need to seek the best management practices for conservation of secondary origin grasslands, climate mitigation and economic sustainability for farmers. The aim of this study was to investigate whether increasing the customary practice of mowing twice a year to monthly mowing through the growing season (when herbage production was feasible; i.e., >0.5 t/ha dry matter) generates changes to the drivers and rates of soil respiration of fertilized Bromus erectus‐ dominated grasslands. Soil CO2 efflux, temperature and moisture were recorded over 3 years (2016–2018) under these "customary" and "monthly" mowing frequencies (twice per year; 4–6 times per year, respectively). Soil CO2 efflux, temperature and moisture were not affected by the higher mowing frequency over the study period. Independent of mowing frequency, soil water content was the main driver of soil CO2 emissions during the growing season (April to October, inclusive), whereas soil temperature was the main driver during the nongrowing season (November to March, inclusive). Therefore, increasing the customary mowing of twice a year to the monthly mowing frequency through the growing season does not impact upon soil respiration of B. erectus ‐dominated grasslands, at least over a 3‐year period.